2004
DOI: 10.1152/ajprenal.00325.2003
|View full text |Cite
|
Sign up to set email alerts
|

Tetanization-induced pelvic-to-pudendal reflex plasticity in anesthetized rats

Abstract: Reflex plasticity between pelvic afferent and pudendal efferent nerve fibers was examined in anesthetized rats. Brief high-frequency electric stimulation (300 pulses at 100 Hz) of the pelvic nerve afferent fiber produced a long-lasting potentiation of the pelvic-to-pudendal reflex (PPR). This tetanization-induced potentiation was abolished by a selective N-methyl-D-aspartate (NMDA) receptor antagonist and attenuated by a non-NMDA excitatory amino acid receptor antagonist. However, the GABA(A)-receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…In the present study, the repetitive stimulation-induced SRP was characterized by a similar NO-dependent sGC/cGMP/ PKG mechanism with LTP in the CA1 area of the hippocampus, indicating a mechanistic link between the repetitive stimulation-induced SRP and the hippocampal LTP (38). This assumption is in accordance with a report that shows that the strength of primary afferent transmission might potentiate following tetanic peripheral inputs (47a).…”
Section: Role Of Ca 2ϩsupporting
confidence: 93%
“…In the present study, the repetitive stimulation-induced SRP was characterized by a similar NO-dependent sGC/cGMP/ PKG mechanism with LTP in the CA1 area of the hippocampus, indicating a mechanistic link between the repetitive stimulation-induced SRP and the hippocampal LTP (38). This assumption is in accordance with a report that shows that the strength of primary afferent transmission might potentiate following tetanic peripheral inputs (47a).…”
Section: Role Of Ca 2ϩsupporting
confidence: 93%
“…These impulses, therefore, induce EUS contraction to establish sufficient intravesical pressure for urine propulsion (11,29). Recent studies investigating SRP in pelvic nerve-to-EUS reflex activity have demonstrated that not only the pelvic nerve-to-EUS reflex activity itself but also the stimulationinduced SRP in such a reflex may play an important role in the urethra closure mechanism (31)(32)(33)(34)(35)(36). In the present study, superimposed pontine tegmentum stimulation produced facilitation in RS-induced SRP in pelvic nerve-to-EUS reflex activity, which suggests that descending modulation coming from the pontine tegmentum may also be essential for the physiological urethra closure functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using in vivo animal preparations, we demonstrated that low-frequency repetitive stimulations (RS) on the pelvic afferent nerve might elicit a novel form of activitydependent reflex plasticity, i.e., a spinal reflex potentiation (SRP) in pelvic nerve-to-EUS reflex activity (9,10,(31)(32)(33)(34)(35)(36). Such an animal model is quite different from investigations using brain or spinal slices with a thickness of several millimeters and may maintain the whole neural network within the central nervous system as well as all the dorsal and ventral rootlets attached on the spinal cord intact, thereby offering a gateway to investigate modulations on the SRP resulting from a specific neuronal projection to the site where SRP occurs.…”
mentioning
confidence: 99%
“…The solution of identical volume to tested agents was dispensed to serve as the vehicle. This selected dose of drug was used because previous studies showed that glutamate and NMDA could induce pelvic-pudendal reflex plasticity in urethane-anesthetized rats at this dose (44,45). Besides, previous studies showed that 5-HT 1A receptor antagonist may modulate micturition reflex at the spinal cord level (20,25,26).…”
Section: Methodsmentioning
confidence: 99%
“…Using in vivo animal preparations, we demonstrated that low-frequency repetitive stimulations (RS) on the pelvic afferent nerve elicited a form of activity-dependent reflex plasticity, spinal reflex potentiation (SRP) in the pelvic-urethra reflex activities (12,13,41,42,43,44,45). Such in vivo preparations used in these studies maintained the whole neural network within the the central nervous system intact, thus offering an animal model to explore the possibility that activity-dependent reflex plasticity can be regulated by a specific nucleus that projects nerve fibers to the site where plasticity occurs.…”
mentioning
confidence: 99%